Foreign Exchange Transactions in the Perspective of Islamic Economics - Hasan, Zulfikar (Eastasouth Institute, 2023)
Judging from its history, the currency has undergone many changes in meaning. Starting from its existence during the barter period to the modern era of money consisting of fiat money and demand deposits. At this time a new term has appeared virtual money. History records that money has developed its meaning, function and value of money. This change automatically has an impact on changes in the law that applies to it. This article uses a qualitative method with a literature study approach. The data presented in this article are sourced from statutory documents, journals, records, and books related to this research. The legal buying and selling of foreign exchange (forex) are permissible, with the following conditions; There is Ijab accompanied by Qabul (there is an agreement to give or receive). As stated in the MUI fatwa that foreign exchange transactions (al-Sharf) are only permitted if there is a need, for example as a precaution and not for speculation (chance) with conditions that have no legal basis.